Recollections of Dante Gabriel Rossetti - Caine, Hall, Sir, 1853-1931 (Salt Lake City, UT : Project Gutenberg, 2008)
"Recollections of Dante Gabriel Rossetti" by Sir Hall Caine is a biographical account written in the late 19th century. The book represents a collection of personal reflections, letters, and critical observations surrounding the life and character of the renowned artist and poet, Dante Gabriel Rossetti. The narrative delves into Rossetti's experiences, friendships, and artistic contributions, providing readers with insights into his psyche and the influences that shaped his work. The opening of this work sets the stage for a deep exploration of Rossetti's life, beginning with his illness and the friendship he developed with Caine through correspondence. The conversation between them hints at the significance of their relationship and Caine's intention to compile Rossetti's letters and recollections as a tribute. Through Caine$1 (Bs voice, we learn about Rossetti's character$1 (Bhis struggles, artistic aspirations, and the complexities of his nature, establishing a foundation for the more detailed accounts of Rossetti$1 (Bs personal and artistic journey that follow in the subsequent chapters. The introduction not only contextualizes Rossetti$1 (Bs life within the artistic movements of his time but also foreshadows the emotional depth and nuance that will characterize this portrayal of the iconic figure. (This is an automatically generated summary.)s
Release date is 2008-05-23
Produced by David Widger
Keywords: Rossetti, Dante Gabriel, 1828-1882